1994
DOI: 10.1111/j.1365-2249.1994.tb06077.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE production in atopic patients is not related to IL-4 production

Abstract: SUMMARYTo analy.se whether there is a general defect in T or B cell function in atopic individuals we have measured cytokine and IgE production by peripheral blood lymphocytes, isolated from 19 atopic donors (17 asthma/rhinitis and two dermatitis patients) in comparison with 19 non-atopic controls. After stimulation oflymphocytes with aiiti-CD2 and anti-CD28. we found no significant difference in IL-2, IL-4 and interferon-gamma (IEN--)) production. To examine the correlation between the production of IgE and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…11a). In human atopic dermatitis, with which murine chronic OXA-DTH bears some resemblance [25], high IgE titres are not necessarily totally dependent on IL-4 [37]. Therefore, it is possible that clarithromycin reduced serum IgE concentration by IL-4-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…11a). In human atopic dermatitis, with which murine chronic OXA-DTH bears some resemblance [25], high IgE titres are not necessarily totally dependent on IL-4 [37]. Therefore, it is possible that clarithromycin reduced serum IgE concentration by IL-4-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We also found extremely poor correlation between IgE and IL-4 production as previously shown by van der Pouw Kraan et al . 30 and surprisingly found correlation of IFN-γ producing T helper cells with total serum IgE in children with AD.…”
Section: Discussionmentioning
confidence: 92%
“…[24] At present, it is well established that cytokines play an important role in many drug-mediated hypersensitivity reactions, ranging from mild rashes to life-threatening reactions. [78910111213141524] However, the potential for specific cytokine (s) to elicit hypersensitivity responses or to contribute to allergic pathogenesis remains largely unexplored in human. Therefore, in this study, we have made an attempt to investigate the role of cytokines in the pathogenesis of pediatric patients which showed hypersensitivity against β-lactam agents.…”
Section: Discussionmentioning
confidence: 99%
“…[710] In many studies, interferon (IFN)-γ production was reported to be essentially normal in atopic subjects,[11] whereas in others, it was markedly reduced[12] or elevated. [13] Interleukin (IL)-4 production was usually[14] but not always[15] reported as substantially higher. In some studies, neither IL-4 nor IFN-γ production was different,[716] whereas in others, synthesis of both cytokines was affected, with IFN-γ inhibited and IL-4 elevated[717] relative to the responses elicited in normal controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation